The Cambridge companion to Jane Austen - Copeland, Edward; McMaster, Juliet (Cambridge, UK New York Cambridge University Press, 2010)
Jane Austen's stock in the popular marketplace has never been higher, while academic studies continue to uncover new aspects of her engagement with her world. This fully updated edition of the acclaimed Cambridge Companion offers clear, accessible coverage of the intricacies of Austen's works in their historical context, with biographical information and suggestions for further reading. Major scholars address Austen's six novels, the letters and other works, in terms accessible to students and the many general readers, as well as to academics. With seven new essays, the Companion now covers topics that have become central to recent Austen studies, for example, gender, sociability, economics, and the increasing number of screen adaptations of the novels--Provided by publisher.
The image that Henry Austen creates - at odds with the evidence that both Austen's letters and her publishing decisions offer of her professionalism - is precisely the one that so annoyed Henry James, according to Brian Southam: 'the myth of the inspired amateur, the homely spinster who put down her knitting needles to take up her pen'. That myth, and others like it, have prevented subsequent readers from understanding that, for Austen, being a professional writer was, apart from her family, more important to her than anything else in her life. Austen wrote when opportunities for women to publish had never been greater, and from her childhood her aim was to see her works in print. She collected her juvenilia in volumes made to resemble published books as closely as possible--Provided by publisher.
Preface / Edward Copeland and Juliet McMaster -- Chronology of Jane Austen's life / Deirdre Le Faye -- 1. The professional woman writer / Jan Fergus -- 2. Northanger Abbey and Sense and Sensibility / Thomas Keymer -- 3. Pride and Prejudice and Mansfield Park / Jocelyn Harris -- 4. Emma and Persuasion / Penny Gay -- 5. The early short fiction / Margaret Anne Doody -- 6. 'Lady Susan', 'The Watsons' and 'Sanditon' / Janet Todd -- 7. The letters / Carol Houlihan Flynn -- 8. Class / Juliet McMaster -- 9. Money / Edward Copeland -- 10. Making a living / David Selwyn -- 11. Gender / E.J. Clery -- 12. Sociability / Gillian Russell -- 13. Jane Austen and literary traditions / Isobel Grundy -- 14. Jane Austen on screen / Kathryn Sutherland -- 15. Austen cults and cultures / Claudia Johnson -- 16. Further reading / Bruce Stovel and Mary M. Chan.
Includes bibliographical references and index.
Keywords: Austen, Jane -- 1775-1817 -- Criticism and interpretation; Women and literature -- England -- History -- 19th century; Romance fiction, English -- History and criticism